Effects of damping-off caused by Rhizoctonia solani anastomosis group 2-1 on roots of wheat and oil seed rape quantified using X-ray computed tomography and real-time PCR - Sturrock, Craig; Woodhall, James; Brown, Matthew; Walker, Catherine; Mooney, Sacha J.; Ray, Rumiana V. (Frontiers, 2015)
Rhizoctonia solani is a plant pathogenic fungus that causes significant establishment and yield losses to several important food crops globally. This is the first application of high resolution X-ray micro Computed Tomography (X-ray μCT) and real-time PCR to study host–pathogen interactions in situ and elucidate the mechanism of Rhizoctonia damping-off disease over a 6-day period caused by R. solani, anastomosis group (AG) 2-1 in wheat (Triticum aestivum cv. Gallant) and oil seed rape (OSR, Brassica napus cv. Marinka). Temporal, non-destructive analysis of root system architectures was performed using RooTrak and validated by the destructive method of root washing. Disease was assessed visually and related to pathogen DNA quantification in soil using real-time PCR. R. solani AG2-1 at similar initial DNA concentrations in soil was capable of causing significant damage to the developing root systems of both wheat and OSR. Disease caused reductions in primary root number, root volume, root surface area, and convex hull which were affected less in the monocotyledonous host. Wheat was more tolerant to the pathogen, exhibited fewer symptoms and developed more complex root systems. In contrast, R. solani caused earlier damage and maceration of the taproot of the dicot, OSR. Disease severity was related to pathogen DNA accumulation in soil only for OSR, however, reductions in root traits were significantly associated with both disease and pathogen DNA. The method offers the first steps in advancing current understanding of soil-borne pathogen behavior in situ at the pore scale, which may lead to the development of mitigation measures to combat disease influence in the field.